Structural Characteristics of Sport Organizations in Kosovo - Iber Alaj; Fitim Arifi; Zenel Metaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Sport in the Constitution of the Republic of Kosovo is defi ned as a special category of social interest and is funded from the budget of the Republic of Kosovo. Subject of this study will be 35 Sports Federations, 867 sports clubs, 67,583 male athletes and 13,458 females. Based on the data of Kosovo Statistical Agency, current condition for sports organizations, clubs, associations, Sports federations as well as sport activities and we will present through the tables underway that will give us a real data for the current condition of the total number of Sports federations, participants in sport activities. For this reason, it is imperative to start with planning and systematic investments in establishing legal infrastructure and structure of sport organizations would be one of the main priorities of the development sports in Kosovo, as another purpose of this paper will be the autonomy of sports and its political neutrality according to international standards, constitutes another priority of the structural organization of organizations or Sports Federations in Kosovo.